Long-term Unemployment and Its Alleviation in Rural Areas – Case of Hungary – - G. Fekete, Éva (Discussion Papers, 2012)
The present research examines the interrelation between long-term unemployment and individual as well as family life strategies, the regional characteristics of the labour market and the territorial development of rural areas, it also explores governmental and local ambitions to alleviate long-term unemployment and evaluate their efficiency. The research presents the regions with the largest concentrations of long-term unemployment and determines its underlying reasons, the interrelation between long-term unemployment and the potential of the social and economic development of the regions, examines central and local attempts to alleviate long-term unemployment, the results of these initiatives and the reasons for their success or failure; presents the foreign models applied in the alleviation of long-term unemployment and the economic sectors most susceptible to employ the long-term unemployed.